SKILLING INDIA’S YOUTH FOR A DIGITAL ECONOMY CHALLENGES AND OPPORTUNITIES IN THE EVOLVING JOB MARKET - Pasha, Mahiboob (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India, with its vast and dynamic youth population, stands at the threshold of a significant economic transformation driven by rapid digitalization. This research paper explores the challenges and opportunities involved in skilling India’s youth to align with the evolving demands of a digital economy. It highlights key issues such as the digital skills gap, accessibility to quality training programs, and regional disparities. Additionally, it examines the potential of government initiatives, public-private partnerships, and educational reforms in addressing these challenges. The paper also emphasizes the role of emerging technologies, such as artificial intelligence, blockchain, and data analytics, in reshaping job roles and creating new career paths. By assessing current frameworks and providing policy recommendations, this study aims to contribute to strategies that will empower India’s youth to thrive in a digital future.